2013
DOI: 10.1016/j.ijsu.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and endovascular treatment for ruptured anterior circulation cerebral aneurysms: A comparison of outcomes – A single centre study from Taiwan

Abstract: The purpose of this 2-year retrospective study is to compare the outcomes of patients with either surgical clipping or endovascular coiling treatment for ruptured anterior circulation cerebral aneurysms. We enrolled 100 patients with spontaneous subarachnoid hemorrhage resulting from ruptured anterior circulation cerebral aneurysms. We reviewed the demographic information, operative details, and image examinations including computed tomography (CT), digital subtraction angiography, and magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In the present article, we find a significantly higher risk of rebleeding in the endovascular coiling group ( p <0.05). Varelas et al [ 33 ] reported that rebleeding was significantly associated with the ventriculoperitoneal shunt ( p <0.05), and some published articles suggested that rebleeding also depended on the follow-up period and on the rate of occlusion after endovascular coiling or microsurgical clipping [ 5 , 7 ] and this meta-analysis also found that clipping was significantly associated with a higher rate of complete occlusion ( p <0.05), this result was consistent with published studies [ 28 , 31 , 35 ]. Murayama et al [ 44 ] also reported that the rate of complete occlusion was found in 55% of aneurysms, and the lesion neck remnant was identified in 35.4% of aneurysms and the rate of recanalization was up to 20.9%, which was associated with the neck of the aneurysm and size of the dome.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present article, we find a significantly higher risk of rebleeding in the endovascular coiling group ( p <0.05). Varelas et al [ 33 ] reported that rebleeding was significantly associated with the ventriculoperitoneal shunt ( p <0.05), and some published articles suggested that rebleeding also depended on the follow-up period and on the rate of occlusion after endovascular coiling or microsurgical clipping [ 5 , 7 ] and this meta-analysis also found that clipping was significantly associated with a higher rate of complete occlusion ( p <0.05), this result was consistent with published studies [ 28 , 31 , 35 ]. Murayama et al [ 44 ] also reported that the rate of complete occlusion was found in 55% of aneurysms, and the lesion neck remnant was identified in 35.4% of aneurysms and the rate of recanalization was up to 20.9%, which was associated with the neck of the aneurysm and size of the dome.…”
Section: Discussionsupporting
confidence: 89%
“…Several articles [ 18 , 19 , 31 , 32 ] demonstrated that a trend toward postoperative rebleeding in the coiling group, while other literatures [ 17 , 33 ] showed the clipping group had a higher rate of rebleeding than the coiling group, and there was no significant difference in their results. In the present article, we find a significantly higher risk of rebleeding in the endovascular coiling group ( p <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles [18,19,31,32] demonstrated that a trend toward postoperative rebleeding in coiling group, while other literatures [30,33,35] showed clipping group had a higher rate of rebleeding than coiling group, and there was not signi cant difference in theirs results.…”
Section: Discussionmentioning
confidence: 98%
“…Ruptured intracranial aneurysm is a life-threatening disease with significant mortality and morbidity rates. 1,2 Patient commonly presents with sudden onset severe headache, which the patient describes as worst headache of life, often with depressed level of consciousness. Early treatment aimed at occlusion of aneurysm is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Ikawa et al 5 in their study of outcome of aneurysmal subarachnoid hemorrhage (SAH) in Japan mentioned that outcomes of aneurysmal SAH may not be the same worldwide. Liao et al 2 in their single center study from Taiwan suggested that the therapeutic outcomes may vary with respect to the available methods, and evaluation of clinical results should be individualized in each medical institute. The purpose of the present study is to retrospectively analyze the baseline characteristics of the patients who have undergone surgical clipping and identify factors affecting outcome, outcome assessment and comparison with results of other such studies.…”
Section: Introductionmentioning
confidence: 99%